Effect of The Dosage and Types of Organic Fertilizer Plant Waste to The Yield of Shallot (Allium ascalonicum L.) - Ika Paridawati; Nurbaiti Amir; Berliana Palmasari; Yusril Esa Mahendra (Universitas Muhammadiyah Palembang, 2024)
The use of organic fertilizers can increase soil fertility and improve the physical, chemical, and biological properties of the soil. This study was to determine the best dosage and types of organic fertilizer from plant waste to the yield of shallot (Allium ascalonicum L.). We conducted this research was conducted on farmer's land in Palembang City, South Sumatra, from May to July 2022. This study used an experimental method with a split plot design consisting of 9 treatment combinations and 3 replications. The first factor (main Plot) of dosage (T), namely T1 = 1 kg per plot; T2 = 3 kg per plot; T3 = 5 kg per plot, while the second factor (sub-plot) is type of organic fertilizer (J), namely J1 = Rice Straw; J2 = Blotong; J3 = Husk Charcoal. Observational variables in this study included number of tillers per clump (saplings), tuber weight per clump (g) and tuber weight per plot (kg). The results showed that tabulated combination of Blotong fertilizer with a dose of 3 kg gave the highest yield of shallots at 0.54 kg per plot or equivalent to 2.16 ha-1.